Impact of Dairy Cooperatives Model Farm (MF) on Milk Production, Cost Competitiveness and Rural Livelihood Improvement in Selected Regions of Bangladesh - Akter, Amrin; Islam, Mohammad Riazul; Sultana, Mst. Nadira; Haque, Mohammad Enamul; Uddin, Mohamamd Helal; Uddin, Mohammad Mohi (Journal of the Bangladesh Agricultural University, 2020)
The aim of present study was to assess Dairy Cooperatives Model Farm (MF-an approach of the Department of Cooperatives) compared with traditional farms in terms of milk productivity and cost of milk production as a measure of cost competitiveness, farm resilience and rural livelihoods of the dairy farmers in four regions of Bangladesh. The holistic approach which combines with research and development agenda was used to handle the complexity of the current dairy farming system and scarcity of data on dairy farms. The International Farm Comparison Network (IFCN) methodology consisting of Typical Farm Approach (TFA), Technology Impact Policy Impact Calculations (TIPICAL) model and dairy networking approach were used. The four regions were selected namely Gopalganj, Tangail, Mymensingh, and Sirajganj purposively where the Dairy Co-operative Model Farm (DCMF) were operating. Data were collected using the IFCN panel approach which is considered as Modified Delphi Technique along with baseline survey, transect survey and panel help survey. Within the DCMF, the 2-cow model farm was selected where under each region first type of farm was Model Farm (MF) with support services where the second farm was Traditional Farm (TF) without any support services. The average milk productivity for MF for all region was higher (1660 kg per cow/year) than TF (1446 kg/cow/year) which is 14.8% higher in MF. The milk productivity has strong regional variations, highest milk production was observed in MF in Sirajganj while the lowest in Gopalganj. The cost of milk production is 7.5% lower in MF than TF where the average cost is 36.44 BDT/kg milk in MF and 39.40 BDT/kg in TF. In relation to cost competitiveness, Gopalganj MF has the lowest cost, implies that highly cost competitive among the regions. The buffer capacity is found to be higher in MF in Tangail and Gopalganj. The Model farms in all regions have increased land, higher income and more income sources than the TF. The study concludes that 2 -cow MF under cooperatives is highly competitive than TF, however, further study might be needed to identify which factors might affect this variation. The results are expected to be beneficial for the policy makers for identifying the suitable farm type and regions for increasing milk production. J Bangladesh Agril Univ 18(3): 708–716, 2020 https://doi.org/10.5455/JBAU.106719